Application of Environmental-Based Scientific Approach to Improve Science Learning Activities and Outcomes in Grade IV Students of SD Inpres Koya, North Morowali Regency - Surahman, Surahman; Suleman, Samsurizal M.; Hatibe, Amiruddin (Jurnal Riset Pendidikan MIPA, 2019)
This study aims to describe an increase in science learning activities and learning outcomes of fourth-grade students through the application of an environment-based scientific approach in the SD Inpres Koya. The research method uses the Hopkins model design, which consists of 4 stages, namely planning, implementation, observation, and reflection. The place for conducting the study was at SD Inpres Koya, from July to August 2018. The research subjects were 12 students. The data collection technique uses observation and test methods. Data analysis was done by analyzing data qualitatively and quantitatively. The results showed that the activity of students increased (15.33%) in the first cycle to the second cycle. Teacher activity increased (14.66%) from the first cycle to the second cycle. Data on student learning outcomes for pre-action classical absorption (57.50%), cycle I (74.14%), and cycle II (85.83%) increased (11.69%). For classical learning completeness pre-action (41.66%), cycle I (75.00%), and cycle II (100%) increased (25.00%). Based on these results, it can be concluded that the application of an environment-based scientific approach can improve the activities and learning outcomes of science in the fourth grade of SD Inpres Koya.